1994
DOI: 10.1136/bjsm.28.2.112
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological survey on ankle sprain.

Abstract: Ankle sprain is a common sports injury and is often regarded as trivial by athletes and coaches. This epidemiological study was conducted among three categories of Hong Kong Chinese athletes: national teams, competitive athletes and recreational athletes. This study shows that as much as 73% of all athletes had recurrent ankle sprain and 59% of these athletes had significant disability and residual symptoms which led to impairment of their athletic performance. This study indicates that a proper approach towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
338
0
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(358 citation statements)
references
References 17 publications
2
338
0
12
Order By: Relevance
“…The attendance rate to A&E for sport-related ankle injuries, ligamentous sprains and fractures were 0.24, 0.19 and 0.02/1000 person-year, which were also less than those recorded by two previous studies at the A&E department -7 in Denmark 15 , and 5.27 in UK 2 . In Hong Kong, a previous study 28 investigating ankle ligamentous sprains on competitive and recreational athletes reported that most sprains were sustained in running and jogging (25%). Another study also showed that lower extremity injuries at the ankle and foot are the major medical problem in running 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The attendance rate to A&E for sport-related ankle injuries, ligamentous sprains and fractures were 0.24, 0.19 and 0.02/1000 person-year, which were also less than those recorded by two previous studies at the A&E department -7 in Denmark 15 , and 5.27 in UK 2 . In Hong Kong, a previous study 28 investigating ankle ligamentous sprains on competitive and recreational athletes reported that most sprains were sustained in running and jogging (25%). Another study also showed that lower extremity injuries at the ankle and foot are the major medical problem in running 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in UK 2 reported the attendance rate to A&E units for patients with ankle ligamentous sprain to be 5.27/1000 person year. Among sports, a survey in Hong Kong reported that most ankle sprains were sustained while pursuing running and jogging activities (25%), racquet sports (20%) and ball games (19%) 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence rates for LASs are high and have been reported to be over 70% (Yeung et al 1994). The reason for the high recurrence rate is believed to be a reduced accuracy of proprioceptive signals from the ankle which leads to a functional instability (Hertel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The attendance rate at a casualty ward was reported to be 7 per 1000 person-years (Holmer et al, 1994). In Hong Kong, a survey on athletes of all levels (national, competitive and recreational) reported that most ankle sprains are sustained in running and jogging (25%), racquet sports (20%) and ball games (19%) (Yeung et al, 1994). However, a recent analysis on medical records (Fong et al, 2006a) from an accident and emergency department reported that most sport-related ankle injuries are sustained from basketball, soccer and hikingThis implied that epidemiology studies should be conducted in different settings to obtain a better overview.…”
Section: Identifying Biomechanics-related Risk Factorsmentioning
confidence: 99%